Exploitation Of Sabbe Sarong In West Nusa Tenggara In Triggering The Economy During The Pandemic - Dewi, Novi Yanti Sandra; dina, Mel; Sulaiman, Jayyyid; Arsyad, Sulaiman (Universitas Muhammadiyah Mataram, 2021)
Abstract: Sabbe sarong is a typical weaving of bugis tribe that has long lived and developed until it is known as a typical handicraft of Tanjung Luar. Because it has been attached and become their trademark, usually this sarong is used instead of a hood. Which, they usually make this sarong in their spare time while waiting for their husbands to go back to sea. However, after this pandemic comes will certainly have an impact on the main livelihood of the people of Tanjung Luar as a fisherman. Therefore, if an action is taken that will have a positive impact on human resources and the region, it will definitely benefit all parties. Therefore, the role of Sabbe Sarong needs to be developed so that regional MSMEs can be applied even in this Pandemic condition. The purpose of this study is to examine more deeply about the exploitation of sabbe holsters in West Lombok so as to improve the economy of the people of the pendemi period, with the method used is qualitative method.Abstrak: Sarung Sabbe merupakan tenunan khas suku bugis yang telah lama hidup dan berkembang hingga dikenal sebagai kerajinan khas Tanjung Luar. Karena telah melekat dan menjadi ciri khas mereka, biasanya sarung ini digunakan sebagai pengganti tudung kepala.Yang mana, mereka biasanya membuat sarung ini di waktu senggang sambil menunggu suami mereka balik melaut. Akan tetapi, setelah pandemi ini datang tentu akan berdampak pada mata pencaharian utama penduduk Tanjung Luar sebagai seorang Nelayan. Untuk itu, jika dilakukan suatu tindakan yang akan berdampak positif terhadap Sumber Daya Manusia dan daerah, pasti akan menguntungkan segala pihak. Oleh sebab itu, peranan Sarung Sabbe ini perlu dikembangkan sehingga UMKM daerah dapat terapkan walaupun dalam kondisi Pandemi ini. Tujuan dari penelitian ini adalah untuk mengkaji lebih Abstract: Sabbe sarong is a typical weaving of bugis tribe that has long lived and developed until it is known as a typical handicraft of Tanjung Luar. Because it has been attached and become their trademark, usually this sarong is used instead of a hood. Which, they usually make this sarong in their spare time while waiting for their husbands to go back to sea. However, after this pandemic comes will certainly have an impact on the main livelihood of the people of Tanjung Luar as a fisherman. Therefore, if an action is taken that will have a positive impact on human resources and the region, it will definitely benefit all parties. Therefore, the role of Sabbe Sarong needs to be developed so that regional MSMEs can be applied even in this Pandemic condition. The purpose of this study is to examine more deeply about the exploitation of sabbe holsters in West Lombok so as to improve the economy of the people of the pendemi period, with the method used is qualitative method.Abstrak: Sarung Sabbe merupakan tenunan khas suku bugis yang telah lama hidup dan berkembang hingga dikenal sebagai kerajinan khas Tanjung Luar. Karena telah melekat dan menjadi ciri khas mereka, biasanya sarung ini digunakan sebagai pengganti tudung kepala.Yang mana, mereka biasanya membuat sarung ini di waktu senggang sambil menunggu suami mereka balik melaut. Akan tetapi, setelah pandemi ini datang tentu akan berdampak pada mata pencaharian utama penduduk Tanjung Luar sebagai seorang Nelayan. Untuk itu, jika dilakukan suatu tindakan yang akan berdampak positif terhadap Sumber Daya Manusia dan daerah, pasti akan menguntungkan segala pihak. Oleh sebab itu, peranan Sarung Sabbe ini perlu dikembangkan sehingga UMKM daerah dapat terapkan walaupun dalam kondisi Pandemi ini. Tujuan dari penelitian ini adalah untuk mengkaji lebih